Improving the character of discipline in role playing through collaborative performance for Indonesia Subject at SMPN 3 Wates Kediri - Sunarno, Sunarno (Prosiding Seminar; 2020: 2020 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.28, 2020)
This research is based on the problem of the low character of discipline in children, the purpose of this study is to increase characterize disciplines in children through the application of role playing methods in collaborating their performance. The research method used is research Classroom Action (CAR) to improve the process of child discipline through the application of role playing methods.  CAR done with two cycles, with the subject of group B children of class X students totaling 10 child. From the results of the implementation and observations made, there was a considerable increase big especially on cycle two. It is recommended for teachers to be disciplined in their respective roles and collaborative skills in performing that can be further developed, both in learning, implementing and learning evaluation